Complete pathological remission and tertiary lymphoid structures are associated with the efficacy of resectable NSCLC receiving neoadjuvant chemoimmunotherapy: A double-center retrospective study - Ying Liu; Lei Xiong; Yue Chen; Ruoxue Cai; Xinyu Xu; Tian Wang; Yiyu Guo; Luxi Ruan; Ying Fang; Quanan Zhang; Bo Shen; Jinjun Ye; et al. (Human Vaccines & Immunotherapeutics)
This study aimed to investigate the relationship between complete pathological remission (PCR), tertiary lymphoid structure (TLS) maturation and expression and clinical outcomes of patients with resectable non-small cell lung cancer (NSCLC) receiving neoadjuvant chemoimmunotherapy. Totally 80 patients with resectable NSCLC (stage IB-IIIB) receiving neoadjuvant chemoimmunotherapy were analyzed. We used the Kaplan-Meier method to plot survival curves and the log-rank test to compare differences. Among all patients included, 45 patients (56.25%) achieved major pathological response (MPR), including 30 patients (37.50%) with PCR. The proportion of patients diagnosed with stage IB, II, IIIA and IIIB was 1.25%, 10.00%, 52.50% and 36.25%, respectively. We divided patients into PCR group and non-PCR group respectively according to whether they achieved PCR. We found that patients achieving PCR had significantly improved disease-free survival (DFS) (mDFS: NR vs. 20.24 months, P = .020). TLS expression was low in 43 cases (53.75%) and high in 37 cases (46.25%). TLS maturation was low in 55 cases (68.75%) and high in 25 cases (31.25%). The DFS of patients with TLS high-maturation (34.07 vs. 22.30 months, P = .024) and TLS high-expression (34.07 vs. 22.30 months, P = .041) was significantly longer. In most subgroups, the PCR, TLS high-maturation and TLS high-expression group respectively achieved a better clinical outcome relative to the non-PCR, TLS low-maturation and TLS low-expression group. In patients with resectable NSCLC receiving neoadjuvant chemoimmunotherapy, the acquirement of PCR may predict better DFS. In addition, high expression and maturation of TLS may be prognostic factors.